REVOLUTION DEVELOPMENT OF DIGITALIZATION AS ASPECT OF CREATIVE AND INNOVATIVE MUHAMMADIYAH YOUTH CHARACTER BUILDING - PRABOWO, ARI; Ahmad Agung Satrio; Nadya Riska Ilmi (Publikasi Pengabdian Masyarakat, 2023)
Digitalization that is developing has an important role for all of Indonesia's young generation by maximizing this moment to upgrade themselves to creative and innovative personal providing easy learning and providing important information with an attractive appearance, so with this it requires perseverance and a sense of trust from young people to form important characters starting from now so that later it will be very beneficial for all levels of society without limiting this knowledge. Youth is an important foundation, especially for Indonesia in the present and future eras to provide an optimal change for the regeneration of a new system that has intellectual, technical and conceptual capabilities that do not abandon Islamic principles in it. So that young people will later have an attitude of firmness and principles of attitude that are in accordance with Islamic teachings by providing the benefits of digitalization-based knowledge. This revolution in the development of digitalization will certainly be an important task for Muhammadiyah youth wherever they are, to maximize the situation so that they continue to be fastabiqul khairat (competition in goodness) to anyone in a neutral manner to have a positive impact on the existing society. Muhammadiyah Youth is one of the autonomous Muhammadiyah organizations, which is an Islamic movement, amar makruf nahi mungkar. Muhammadiyah Youth was founded with the aim of gathering, fostering, and mobilizing Islamic youth and increasing their role as cadres to achieve Muhammadiyah goals. Muhammadiyah Youth was founded with the aim of gathering, fostering, and mobilizing Islamic youth and increasing their role as cadres to achieve Muhammadiyah goals. Its vision and mission is to become Muhammadiyah Youth who are superior, independent, independent, transformative and play a national and global role in 2022. Encourage and facilitate Muhammadiyah Youth cadres to develop their own potential. Developing the economic potential and autonomy of Muhammadiyah Youth. Keywords: Creative, Innovative, Character, Digitalization